Prognostic significance of ischemia-modified albumin in acute ischemic stroke patients: A preliminary study - Nayak, Amit R (Indian Academy of Neurosciences, 2011)
BACKGROUND: Ischemia-modified albumin (IMA) is a sensitive marker of ischemic event. However, limited studies are available regarding role of IMA in acute ischemic stroke (AIS). PURPOSE: The aim of this study was to evaluate time course of IMA in AIS patient to validate its prognostic value. METHODS: IMA level was estimated in serum samples collected from five AIS patients at admission, 24hrs, 48hrs, 72hrs, and 144hrs after admission and also from five control subjects. RESULTS: There was significant (p<0.05) increase in IMA level in AIS samples at admission, 24hrs, 48hrs and 144hrs respectively when compared with control. On comparing IMA levels in follow up AIS samples with that of admission value we found that it decreased in follow-up samples till 72hrs, and significant (p<0.05) decrease was observed at 24hrs and 72hrs. CONCLUSION: Findings shows that follow up estimation of IMA level in AIS may help in the prediction of the clinical status and outcome.